Evidence of Second Canal between Permanent Mandibular Central and Lateral Incisors in China; a Systematic Review on CBCT Studies - Nyan M. Aung; Kyaw K. Myint (International Journal of Dentistry)
Introduction. Evidence of second canal in permanent mandibular incisors is frequently questioned in dentistry. The difference in evidence between the two teeth is an interesting argument across different countries and ethnicities. So the aim of the systematic review was to investigate the evidence of second canal between permanent mandibular central and lateral incisors in China. Materials and Methods. The papers were selected from the electronic databases and hand searching according to inclusion and exclusion criteria. All qualified studies were judged by the reviewers. The selected studies were checked with Joanna Briggs Institute Critical Appraisal tool for prevalence studies. Finally, three studies were selected for the review and meta-analyses. The proportion of the second canal with its confidence interval and forest plot for the meta-analyses were calculated. Results. The evidences of second canal in permanent mandibular central and lateral incisors in China were 5.6% and 14.1%. Only one study reported bilateral symmetry of the second canal as 58.7% and 76.1% in the two types of teeth. Out of all canal anatomies, Vertucci’s type ΙΙΙ was dominant comprising 4.1% and 11.2% together with other second-canal types comprising 1.4% and 3% in permanent mandibular central and lateral incisors. When the proportions were meta-analyzed, mandibular central incisors had been less numerous OR = 0.35 [0.31, 0.40], 0.33[0.28, 0.39], and 0.42 [0.22, 0.79] in the evidence of second canal, of Type ΙΙΙ, and of other types except Type ΙΙΙ than mandibular lateral incisors in China. Out of all second-canal anatomies, Type ΙΙΙ presented 72.5% and 78.9% along with other second-canal types comprising 24.3% and 21.1% in the two teeth in China. Discussion. There was the evidence of second canal which deviated toward the permanent mandibular lateral incisor also in case of bilateral symmetry, the prevalence of Vertucci’s Type ΙΙΙ, and other second-canal types out of all canal anatomies.